2017
DOI: 10.1016/j.biomaterials.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Peptide valency plays an important role in the activity of a synthetic fibrin-crosslinking polymer

Abstract: Therapeutic polymers have the potential to improve the standard of care for hemorrhage, or uncontrolled bleeding, as synthetic hemostats. PolySTAT, a fibrin-crosslinking peptide-polymer conjugate, has the capacity to rescue fibrin clot formation and improve survival in a model of acute traumatic bleeding. PolySTAT consists of a synthetic polymer backbone to which targeting fibrin-binding peptides are linked. For translation of PolySTAT, the optimal valency of peptides must be determined. Grafting of fibrin-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…In vitro and in vivo studies have shown its beneficial effects on clot formation by crosslinking fibrin and potential use in transfusion for the treatment of coagulopathy and hemorrhage control in a rat femoral artery injury model [50,126]. A recent study showed the binding and augmentation of clot formation through multivalent display of the fibrin-binding peptides along the polymer backbone and the optimal valency of four peptides per polymer for maximum hemostatic function [51]. In addition, when loaded onto a nonwoven chitosan gauze, the PolySTAT/chitosan composite gauze reduced blood loss and improved the survival rate compared to a commercial hemostatic gauze (Celox Rapid) in a rat model of femoral artery injury [127].…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…In vitro and in vivo studies have shown its beneficial effects on clot formation by crosslinking fibrin and potential use in transfusion for the treatment of coagulopathy and hemorrhage control in a rat femoral artery injury model [50,126]. A recent study showed the binding and augmentation of clot formation through multivalent display of the fibrin-binding peptides along the polymer backbone and the optimal valency of four peptides per polymer for maximum hemostatic function [51]. In addition, when loaded onto a nonwoven chitosan gauze, the PolySTAT/chitosan composite gauze reduced blood loss and improved the survival rate compared to a commercial hemostatic gauze (Celox Rapid) in a rat model of femoral artery injury [127].…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…The PolySTATs having a valency of four and higher showed increased clot firmness and formation rates with lower clot breakdown. Lamm et al, have shown that the quadrivalent PolySTATs increased clot firmness values by 57% and decreased the breakdown values by 69% as compared to phosphate-buffered saline [133]. Furthermore, Lamm et al, also carried out an experiment with PolySTAT to optimize its yield and synthesis method, which could potentially capacitate mass production of PolySTAT and its clinical translation [134].…”
Section: Polystatmentioning
confidence: 99%
“…PolySTAT binds fibrin strands together, reinforcing the fibrin network and increasing the overall strength of the clot. [51][52][53][54] In a rat femoral artery injury model, 100% of animals treated with PolySTAT survived the observation period, compared with 40% of rats receiving saline. Other strategies use hyaluronic acid (HA) or polyethylene glycol backbones conjugated with a peptide that can be recognized and crosslinked by FXIII-A*.…”
Section: Peptide-polymer Conjugatesmentioning
confidence: 99%